Peran Mahkamah Internasional (ICJ) Dalam Mengatasi Pelanggaran Hukum Humaniter Di Palestina 2023-2024 - Ahmad, S. Thoriq Musthofa; Muhammad Reyhan; Sepana Virqiyan (Talenta Publisher, Universitas Sumatera Utara, 2024)
This study discusses the role played by the International Court of Justice (ICJ) in overcoming humanitarian law in Palestine in 2023-2024, various efforts have been made by the International Court of Justice in addressing the issue of genocide, including taking a role in the international reports submitted to the International Court of Justice on what happened in Palestine, as an international judicial institution The International Court of Justice (ICJ) has an important role in dealing with human rights violations and international crimes. One of the issues that has always been in the spotlight is the conflict in Palestine and Israel, which is often colored by accusations of genocide by several countries.